Perfect weight : The Complete Mind/Body Programme for Maintaining Your Ideal Weight - Chopra, Deepak (London Rider, 1994)
Draws on the ancient Indian system of medicine called Ayurveda, and Western scientific research, to offer specific strategies for permanent weight loss. By understanding the interaction between mind and body Dr Chopra shows that you can lose weight successfully without the pressure of dieting.
Include Index and Colour Illustration
Keywords: Weight loss -- Medicine, Ayurvedic -- Mind and body